Preparation method of acetone sensor based on MXene material
The organ-like MXene V4C3Tx was prepared by etching the MAX phase V4AlC3 by acid, which solved the problem of detection of acetone gas at room temperature in the prior art, and achieved low operating temperature, low detection limit and high selective detection effects.
Patent Information
- Application Number
- CN202410570966.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-09
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to detect acetone gases with high sensitivity, low detection limits and high selectivity at room temperature, especially in a mixture of acetone and water vapor.
The organ-like MXene V4C3Tx was prepared by acid etching the MAX phase V4AlC3 as a precursor by acid method, and the Al layer in V4AlC3 was selectively etched at room temperature using Al and Co as catalysts to form a V4C3Tx nanomaterial with semiconductor characteristics.
It realizes a low detection limit of 1 ppm and high selectivity detection of acetone at a low operating temperature of 25°C. It has ultra-sensitive and highly selective gas sensing properties, and is suitable for acetone detection in room temperature environments.
Smart Images

Figure CN119643654A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of MXene preparation, and in particular to accordion-shaped V4C3T x Materials, preparation methods and applications thereof. The accordion-shaped MXene was prepared by acid etching with MAX phase V4AlC3 as a precursor. V4AlC3 was used as a raw material. A new type of MXene, V4C3T, was prepared by selectively etching the Al layer at room temperature (RT). x This nanomaterial can be used as a room temperature gas-sensitive sensing material and has high selectivity for acetone in a mixed gas of acetone and water vapor, and can be used to sensitively detect acetone gas in the mixed gas. Background Art
[0002] According to the China Diabetes Report, the number of diabetes patients has increased from 90 million to 140 million in 2021 in the past 10 years, an increase of 56%. Among them, about 70 million patients have not yet been diagnosed, accounting for 51.7%. Researchers found that the patient's blood ketone concentration has a nearly linear correlation with the acetone concentration in the breath. This discovery means that we can detect the blood ketone concentration by checking the acetone concentration in the exhaled breath. The two-dimensional graphene-like material Mxenes is a new material that has just appeared in recent years. As a metal-like material, it has an extremely low resistance value and can achieve room temperature sensing. It is very necessary and practical to study and invent a highly responsive, highly sensitive and stable acetone room temperature gas-sensitive material. Obviously, using V4C3T x The acetone sensor made of MXene material gives the material good selection specificity, low detection limit, high sensitivity, repeatability and the possibility of working at room temperature, providing a new idea for detecting acetone in room temperature environment. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a novel semiconductor oxide (V4C3T for short) with rich surface groups, microporosity, large specific surface area, uniform particle size, good chemical stability and good electrical conductivity in view of the shortcomings and defects mentioned in the background technology. x ) material, the nanomaterial can achieve a low operating temperature of 25 °C, a low detection limit of 1 ppm and a highly selective room-temperature sensing detection of acetone in a mixed gas of acetone and water vapor.
[0004] In order to solve the above technical problems, the technical solution proposed by the present invention is: V4C3T of the present invention x Nanomaterials, using Al and Co as catalysts, synthesized a new MXene V4C3T via V4AlC3 x, and selectively etched the Al layer in V4AlC3 using HF aqueous solution at room temperature. After HF treatment, V4C3T x MXene changes from metal V4AlC3a to semiconductor. It is worth noting that V4C3T x MXene exhibits good acetone sensing performance with an operating temperature as low as 25 °C and a detection limit as low as 1 ppm.
[0005] Thanks to V4C3T x Due to the large surface area and unique atomic structure of the film, it shows great potential for ultrasensitive and highly selective gas sensing. x Thin-film sensing device, applying a DC voltage between two copper electrodes. Collecting V4C3T x The resistance of the film is used as the sensing signal. V4C3T x The sheet resistivity of the film is calculated to be ~1000 ㏁sq -1 , making ultra-low power sensor nodes for Internet of Things (IoT) applications possible. The sensor device was placed in a sealed chamber, where different concentrations of acetone vapor were mixed with nitrogen as carrier gas by atmospheric pressure gas flow mixing method, as described in our previous work. Therefore, this shows that acetone has a significant effect on V4C3T x The film is sensitive and can be detected accurately.
[0006] As a general inventive concept, the present invention provides, on the other hand, the novel MXene phase V4C3T x The material preparation method comprises the following steps: (1) Preparation of polymer flexible substrate: After cutting the flexible nylon substrate, ultrasonically clean it with deionized water, acetone and ethanol respectively. After drying the substrate with nitrogen, magnetron sputtering technology is used to sputter interdigitated electrodes on the substrate through the engraved template for future use.
[0007] (2)V4C3T x Material preparation: V4C3T is prepared using V4AlC3 material x ; First, 1g V4AlC3 single crystal was ground into powder using a mortar, and then soaked in 20 mL of 40% HF solution at room temperature for 5 days. Then the obtained solution was vacuum filtered, and V4C3T was obtained by filtration and freeze drying at a temperature of -20°C and a vacuum of 5 Pa. x The powder is used for further characterization and experimental purposes. The above preparation method preferably comprises the following steps: Step (1) Preparation of polymer flexible substrate: Cut the flexible nylon substrate into a length of 15 mm and a width of 15 mm, and ultrasonically clean it with deionized water, acetone and ethanol respectively, with an ultrasonic frequency of 30-50 KHz and an ultrasonic cleaning time of 5-15 min. After the substrate is blown dry with nitrogen, a magnetron sputtering technique is used to sputter a 10 mm long and 1 mm wide interdigitated electrode onto the substrate through an engraved template, which is then set aside for use.
[0008] Step (2) Preparation of V4C3T x The preparation method of acetone gas-sensitive material is as follows: First, 1g V4AlC3 single crystal is ground into powder with mortar, and then soaked in 20mL of 40% HF solution at room temperature for 5 days. Then the obtained solution is filtered under vacuum, and then washed with deionized water until the pH value reaches 6. Finally, V4C3T is obtained by filtration and freeze drying at temperature: -20 ℃ and vacuum: 5 Pa. x Powder for further characterization and experimental purposes. 1g of V4AlC3 was completely converted into 0.9g of V4C3T after HF etching for 5 days. x .
[0009] Step (3), V4C3T x Preparation of nanosheets: V4C3T x The powder was dispersed in deionized water and then sonicated in an ice bath for 5 h using a 200 W ultrasonic machine. The mixture was centrifuged at 3000 rpm for 20 min, and the resulting suspension was freeze-dried at -20 °C and 5 Pa vacuum to obtain the final product, V4C3T x Nanosheets were collected for further characterization and experimental use. In addition, it should be noted that if only V4C3T x The powder was simply sonicated and centrifuged, V4C3T x The yield of nanosheets is less than 20%. In order to improve the production efficiency, tetrabutylammonium hydroxide (TBAOH) was used to intercalate V4C3Tx powder for stratification. First, 0.5 g V4C3T x The powder was treated with a 30% TBAOH solution for 6 h. Then, it was centrifuged at 10,000 rpm for 20 min to obtain TBAOH-treated V4C3T x Again, the TBAOH-treated MXene was mixed with deionized water and then hand-shaken for 3 min. Finally, the whole mixture was centrifuged at 3000 rpm for 20 min, the black supernatant was separated from the unstratified MXenes, and the obtained suspension was freeze-dried at temperature: -20 °C and vacuum: 5 Pa to obtain about 0.4 g of V4C3T xInterestingly, we found that the delamination agent TBAOH can be used to delaminate V4C3T x The yield of nanosheets increased from 25% to 80%.
[0010] Step (4), V4C3T x Preparation of quantum dots: First, 1g of V4AlC3 single crystal was ground into powder using a mortar, and then soaked in 48ml of 40% HF solution at room temperature for 10 days. Then the obtained solution filtrate was soaked and washed alternately with deionized water until the pH value reached 6. Secondly, the mixture was mixed with deionized water and then ultrasonicated in an ice bath for 2 h at an ultrasonic power of 200w. Centrifuged at 10000 rpm for 20 min, and then freeze-dried at temperature: -20℃, vacuum: 5 Pa, and finally 0.5g V4C3T was obtained. x Nano dots. In the above preparation method, preferably, in the step (1), the nylon substrate is cut into a length of 15 mm and a width of 15 mm, the ultrasonic washing is performed at an ultrasonic frequency of 40 KHz and a ultrasonic washing time of 10 min, and after the substrate is blown dry with nitrogen for 5 min, a magnetron sputtering technique is used to sputter an interdigitated electrode with a length of 10 mm and a width of 1 mm onto the substrate through an engraved template, and the electrode is set aside for use.
[0011] The present invention also provides an application, wherein the Ti3C2T x / WO3 / Au nanocomposite materials are used as room temperature gas sensitive sensing materials, mainly for detecting acetone in mixed gases.
[0012] The technical effects of the present invention are: Thanks to V4C3T x The large surface area and unique atomic structure of the film show great potential for ultra-sensitive and highly selective gas sensing. On the one hand, MXene has an accordion-like geometric structure. The introduction of MXene has a large interlayer gap that can provide a large number of gas adsorption sites. The V4C3Tx film shows high selectivity for acetone (sub-ppm) in water vapor at room temperature, among which V4C3T x The sensor has excellent sensing performance for the adsorption of acetone. Acetone is adsorbed on the surface of the tri-coordinated V (V 3c ) atoms, forming V-C and V-O bonds, while water is adsorbed on the surface V 3c atoms, forming an O-V bond parallel to the surface V-C bond. 3cOur DFT calculations show that the adsorption energies of acetone and H2O on the V4C3 monolayer are -1.11 and -1.97 eV, respectively, which is consistent with the order of the VO bond lengths (2.22 Å and 2.09 Å). The adsorption behavior is quite different (0.86 eV), corresponding to the V4C3T x Sensitivity to acetone. Therefore, high-sensitivity detection of acetone can be achieved at room temperature with good repeatability, fast response and good chemical stability.
[0013] V4C3T x The material was deposited onto a cheap polymer flexible substrate to obtain a flexible room-temperature acetone sensor with high sensitivity based on the sensitive material. Different electrodes can be deposited on the flexible substrate. It has low cost, simple and controllable steps, good flexibility, high sensitivity, can detect acetone at room temperature, and has great hope of being applied in people's real life.
[0014] Compared with the prior art, the present invention provides a novel MXene V4C3T synthesized by using Al and Co as catalysts through V4AlC3 x , and selectively etched the Al layer in V4AlC3 using HF aqueous solution at room temperature. After HF treatment, V4C3T x MXene changes from metallic V4AlC3a to semiconductor. It is worth noting that V4C3T x MXene exhibits good acetone sensing performance with an operating temperature as low as 25 °C and a detection limit as low as 1 ppm. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0016] Figure 1 V4C3T prepared in the embodiment of the present invention x SEM image of gas-sensitive material.
[0017] Figure 2 V4C3T at room temperature in the embodiment of the present invention x Sensor response of the membrane to different concentrations of acetone (0.5 ppm to 8 ppm); the inset is the response to 0.5 PPM acetone Figure 3 Embodiment 3 of the present invention V4C3T x Comparison of the gas-sensitive responses of the membranes to 10% acetone (v / v) and 10% H2O (v / v).
[0018] Figure 4 It is V4C3T x Gas-sensitive responses of the film at different temperatures of 25 ℃, 50 ℃ and 100 ℃.
[0019] Figure 5 Sensor electrode installation diagram In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical scheme of the present invention is now described in detail below in conjunction with specific embodiments. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Example
[0020] An accordion-shaped MXene: V4AlC3 was prepared by selectively etching the Al layer in V4AlC3 with HF aqueous solution at room temperature using Al and Co as catalysts. x The preparation method of gas-sensitive materials used in the field of acetone detection is as follows: (1) The flexible nylon substrate was cut into pieces with a length of 15 mm and a width of 15 mm. The pieces were ultrasonically cleaned with deionized water, acetone, and ethanol, respectively, at an ultrasonic frequency of 40 kHz and for 10 min. The substrate was blown dry with nitrogen for 5 min, and then magnetron sputtering technology was used to sputter interdigital electrodes with a length of 10 mm and a width of 1 mm onto the substrate through the engraved template. The electrodes were set aside for later use.
[0021] Step (2), preparation of V4C3T x The preparation method of acetone gas-sensitive material is as follows: First, 1g V4AlC3 single crystal is ground into powder with mortar, and then soaked in 20mL of 40% HF solution at room temperature for 5 days. Then the obtained solution is filtered under vacuum, and then washed with deionized water until the pH value reaches 6. Finally, V4C3T is obtained by filtration and freeze drying at temperature: -20 ℃ and vacuum: 5 Pa. x Powder for further characterization and experimental purposes. 1g of V4AlC3 was completely converted into 0.9g of V4C3T after HF etching for 5 days. x .
[0022] Step (3), V4C3T x Preparation of nanosheets: V4C3T x The powder was dispersed in deionized water and then sonicated in an ice bath for 5 h using a 200 W ultrasonic machine. The mixture was centrifuged at 3000 rpm for 20 min, and the resulting suspension was freeze-dried at -20 °C and 5 Pa vacuum to obtain the final product, V4C3T x Nanosheets were collected for further characterization and experimental use. In addition, it should be noted that if only V4C3T x The powder was simply sonicated and centrifuged, V4C3T xThe yield of nanosheets is less than 20%. In order to improve the production efficiency, tetrabutylammonium hydroxide (TBAOH) was used to intercalate V4C3Tx powder for stratification. First, 0.5 g V4C3T x The powder was treated with a 30% TBAOH solution for 6 h. Then, it was centrifuged at 10,000 rpm for 20 min to obtain TBAOH-treated V4C3T x Again, the TBAOH-treated MXene was mixed with deionized water and then hand-shaken for 3 min. Finally, the whole mixture was centrifuged at 3000 rpm for 20 min, the black supernatant was separated from the unstratified MXenes, and the obtained suspension was freeze-dried at temperature: -20 °C and vacuum: 5 Pa to obtain about 0.4 g of V4C3T x Interestingly, we found that the delamination agent TBAOH can be used to delaminate V4C3T x The yield of nanosheets increased from 25% to 80%.
[0023] Step (4), V4C3T x Preparation of quantum dots: First, 1g of V4AlC3 single crystal was ground into powder using a mortar, and then soaked in 48ml of 40% HF solution at room temperature for 10 days. Then the obtained solution filtrate was soaked and washed alternately with deionized water until the pH value reached 6. Secondly, the mixture was mixed with deionized water and then ultrasonicated in an ice bath for 2 h at an ultrasonic power of 200w. Centrifuged at 10000 rpm for 20 min, and then freeze-dried at temperature: -20℃, vacuum: 5 Pa, and finally 0.5g V4C3T was obtained. x Nano dots. After being placed in a freeze dryer for 12-48 h, V4C3T was obtained. x Material: 5-20 mg of the material obtained in step (4) is dispersed in 50-200 μL of deionized water, and is drop-casted onto the substrate obtained in step (1) using a pipette using a solid solution drop-casting method and allowed to dry naturally.
[0024] Step (5), sensing measurement: In the sensing experiment and characterization, the film obtained by vacuum filtration was freeze-dried, peeled and cut into the required thin sheets, and two copper wires were connected to V4C3T using silver colloid. x The two ends of the film act as electrodes. A DC voltage is applied between the two electrodes to collect V4C3T x The resistance of the film is used as the sensing signal. After calculation, V4C3T x The sheet resistance of the film is ~100 ㏁, which enables low-power operation of the sensor and meets the requirements of ultra-low-power sensor nodes in IoT applications. The sensor device was placed in a sealed chamber and injected with acetone vapor at different concentrations under a nitrogen background.
[0025] 1. Preparation of V4C3T using V4AlC3 according to claim 1 x Preparation method of acetone gas sensitive material. x The powder was dispersed in deionized water and then sonicated in an ice bath for 5 h using a 200 W ultrasonic machine. The mixture was centrifuged at 3000 rpm for 20 min, and the resulting suspension was freeze-dried at -20 °C and 5 Pa vacuum to obtain the final product, V4C3T x The nanosheets were transferred to the flexible substrate obtained in step (1) and dried naturally for 24 h.
[0026] The advantage of this embodiment is that we found that using the delamination agent TBAOH can x The yield of the nanosheets increased from 25% to 80%. The selectivity of acetone and water vapor at low concentrations from 1ppm to 100ppm. This shows that the sensor has a significant response to acetone in a wide range, while almost no signal of water vapor is detected, indicating the selectivity for acetone over water molecules at low detection limits.
[0027] Experimental testing Apply a DC voltage between two copper electrodes. Collect V4C3T x The resistance of the film is used as the sensing signal. V4C3T x The sheet resistivity of the film was calculated to be ~1000 ㏁sq-1, enabling ultra-low power sensor nodes for Internet of Things (IoT) applications. The sensor device was placed in a sealed chamber where different concentrations of acetone vapor were introduced with nitrogen as carrier gas via an atmospheric pressure gas flow mixing method as described in our previous work. Therefore, this indicates that acetone has a significant effect on V4C3T x The film is sensitive and can be detected accurately.
[0028] like Figure 2 It is noteworthy that the total resistance change for 1 ppm acetone is 5%, which is better than other reported state-of-the-art solid-state acetone sensors at room temperature.
[0029] The present invention also characterizes the selectivity of the acetone sensor to water molecules, such as Figure 3 At the same concentration, i.e. 10% v / v, the resistance change of acetone vapor is >104 larger than that of water vapor. This is much better than the high selectivity between acetone and water vapor reported recently based on proton current measurements. Figure 3The inset shows the selectivity of acetone and water vapor at low concentrations from 1 ppm to 100 ppm. This shows that the sensor has a significant response to acetone over a wide range, while almost no signal is detected for water vapor, indicating the selectivity for acetone over water molecules at low detection limits. In addition, the rise time (required to reach 90% of the maximum sensor response) for the acetone response (~40 s) is also much shorter than that for the water vapor response (~510 s).
[0030] The above embodiments provide a detailed introduction to the products and methods of the present invention. Specific examples are used herein to illustrate the main steps and implementation methods of the present invention. The above embodiments are only to help understand the methods and core principles of the present invention. For those skilled in the art, according to the core principles of the present invention, various conditions and parameters may be changed as needed in specific implementations. In summary, this specification should not be construed as limiting the present invention.
Claims
1. A method for preparing an acetone sensor based on MXene material, characterized in that: The specific steps are as follows: Step (1), preparation of a polymer flexible substrate: a flexible nylon substrate is cut into pieces with a length of 15 mm and a width of 15 mm, and ultrasonically cleaned with deionized water, acetone and ethanol in sequence, with an ultrasonic frequency of 30 to 50 KHz and an ultrasonic cleaning time of 5 to 15 min. The substrate is blown dry with nitrogen, and then a magnetron sputtering technique is used to sputter interdigital electrodes with a length of 10 mm and a width of 1 mm onto the substrate through an engraved template, and the electrodes are set aside for use; Step (2), preparation of V4C3T x The preparation method of acetone gas-sensitive material is as follows: First, 1g V4AlC3 single crystal is ground into powder with mortar, and then soaked in 20mL of 40% HF solution at room temperature for 5 days. Then the obtained solution is filtered under vacuum, and then washed with deionized water until the pH value reaches 6. Finally, V4C3T is obtained by filtration and freeze drying at temperature: -20 ℃ and vacuum: 5 Pa. x Powder for further characterization and experimental purposes. 1g of V4AlC3 was completely converted into 0.9g of V4C3T after HF etching for 5 days. x .
2. Step (3), V4C3T x Preparation of nanosheets: V4C3T x The powder was dispersed in deionized water and then sonicated in an ice bath for 5 h using a 200 W ultrasonic machine. The mixture was centrifuged at 3000 rpm for 20 min, and the resulting suspension was freeze-dried at -20 °C and 5 Pa vacuum to obtain the final product, V4C3T x Nanosheets were collected for further characterization and experimental use. In addition, it should be noted that if only V4C3T x The powder was simply sonicated and centrifuged, V4C3T x The yield of nanosheets is less than 20%. In order to improve the production efficiency, tetrabutylammonium hydroxide (TBAOH) was used to intercalate V4C3Tx powder for stratification. First, 0.5 g V4C3T x The powder was treated with a 30% TBAOH solution for 6 h. Then, it was centrifuged at 10,000 rpm for 20 min to obtain TBAOH-treated V4C3T x Again, the TBAOH-treated MXene was mixed with deionized water and then hand-shaken for 3 min. Finally, the whole mixture was centrifuged at 3000 rpm for 20 min, the black supernatant was separated from the unstratified MXenes, and the obtained suspension was freeze-dried at temperature: -20 °C and vacuum: 5 Pa to obtain about 0.4 g of V4C3T x Nanosheets.
3. Step (4), V4C3T x Preparation of quantum dots: First, 1g V4AlC3 single crystal was ground into powder using a mortar, and then soaked in 48ml of 40% HF solution at room temperature for 10 days. Then the obtained solution filtrate was soaked and washed alternately with deionized water until the pH value reached 6. Secondly, the mixture was mixed with deionized water and then ultrasonicated in an ice bath for 2 h at an ultrasonic power of 200w. Centrifuged at 10000 rpm for 20 min, and then freeze-dried at temperature: -20℃, vacuum: 5 Pa, and finally 0.5g V4C3T was obtained. x Nanodots.
4. Place in freeze dryer and dry for 12-48 hours to obtain V4C3T x Material: 5-20 mg of the material obtained in step (4) is dispersed in 50-200 μL of deionized water, and is drop-casted onto the substrate obtained in step (1) using a pipette using a solid solution drop-casting method and allowed to dry naturally.
5. Step (5), sensing measurement: In the sensing experiment and characterization, the film obtained by vacuum filtration was freeze-dried, peeled and cut into the required thin sheets, and two copper wires were connected to V4C3T using silver colloid. x The two ends of the film act as electrodes. A DC voltage is applied between the two electrodes to collect V4C3T x The resistance of the film is used as the sensing signal. After calculation, V4C3T x The sheet resistance of the film is ~100 ㏁, which enables low-power operation of the sensor and meets the requirements of ultra-low-power sensor nodes in IoT applications. The sensor device was placed in a sealed chamber and injected with acetone vapor at different concentrations under a nitrogen background.
6. The method for preparing V4C3T using V4AlC3 according to claim 1 x Preparation method of acetone gas sensitive material. x The powder was dispersed in deionized water and then sonicated in an ice bath for 5 h using a 200 W ultrasonic machine. The mixture was centrifuged at 3000 rpm for 20 min, and the resulting suspension was freeze-dried at -20 °C and 5 Pa vacuum to obtain the final product, V4C3T x The nanosheets were transferred to the flexible substrate obtained in step (1) and dried naturally for 24 h.